2013
DOI: 10.4103/0974-2727.115923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Zinc Status and Glycated Hemoglobin of Type 2 Diabetes Mellitus Patients in a Tertiary Care Hospital of Assam

Abstract: The present study was undertaken to find out any correlation between serum zinc concentration and HbA1C% in patients with type 2 diabetes mellitus (DM). The study was carried out on 50 newly diagnosed patients of type 2 diabetes and controls in the Department of Biochemistry, Assam Medical College and Hospital, Dibrugarh. Analyses of blood glucose (fasting and postprandial), glycated hemoglobin (HbA1c), serum zinc, urea, and creatinine concentrations were performed by standard methods. Concentrations of fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
4
21
1
Order By: Relevance
“…However, in type-1 diabetes, studies have reported a negative effect of zinc supplementation on glucose homeostasis [104]. …”
Section: Deficiency Of Zinc In Diabetes Mellitusmentioning
confidence: 99%
“…However, in type-1 diabetes, studies have reported a negative effect of zinc supplementation on glucose homeostasis [104]. …”
Section: Deficiency Of Zinc In Diabetes Mellitusmentioning
confidence: 99%
“…In the present study cohort with prediabetes, baseline serum zinc concentrations at the initiation of the clinical trial were below normal. The presence of hypozincemia in established T2DM has been demonstrated by numerous studies, and zinc deficiency is postulated to be at least partially responsible for the high diabetes epidemicity observed in developing countries, especially in the Asia–Pacific region . However, whether hypozincemia precedes diabetes or vice versa (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1 According to the data published by International Diabetes Federation in their 5th edition of Diabetes Atlas, people living with diabetes is expected to rise from 366 million in 2011 to 552 million by 2030. 2 It is identified that zinc plays an important role in synthesis, storage and secretion of insulin in response to carbohydrate intake and plays an important role in energy production. It also maintains the structural integrity of insulin.…”
Section: Introductionmentioning
confidence: 99%